(untitled) (Swiss Medical Weekly, 2020)
Malnutrition has been defined as a “state resulting from lack of uptake or intake of nutrition, leading to altered body composition and body cell mass, as well as to diminished physical and mental function and impaired clinical outcome from disease.” Particularly for the multimorbid medical inpatient, there are multiple research studies linking malnutrition to adverse clinical outcomes independent of type of acute and chronic illnesses. Importantly, recent trials have shown that malnutrition is indeed a modifiable risk factor with specific individualised nutritional support interventions started at hospital admission having positive effects on the risk of complications, mortality, functional outcomes, rehospitalisation and quality of life. Understanding the optimal use of nutritional support in patients with acute illness is complex – as timing, route of delivery, and the amount and type of nutrients can all affect patient outcome. The aim of this narrative review is to provide a practical guideline for pragmatic and evidence-based assessment and treatment of medical inpatients at nutritional risk. We thereby focus on screening, patient assessment, definition of individual nutritional goals and nutritional support interventions that help patients to reach these goals.